Energy Efficiency in Industrial Areas: Application of Best Practices for Energy Efficiency In Mediterranean Industrial Areas - Segreto, Maria-Anna; Artioli, Marcello; Preka, Rovena; Tarantini, Mario (European Journal of Sustainable Development, 2013)
The results presented in this paper originate from an EU research project that is near toits completion. The goal was to build a model that can be applied to all industrial sites inthe Mediterranean area. The approach followed to achieve the objectives was to study allthe new technologies and systems that, if applied globally, can make the whole areasustainable both energetically and environmentally. The application of the model allowsthe design and implementation of self-sufficient green areas in terms of energy which alsobrings to the reduction of the emissions into the atmosphere. An aim of the project wasalso to identify possible sources of funding or incentives. The main beneficiaries of theresults are SMEs that through a more responsible approach to the environment could getgreater market competitiveness and reduce energy costs of their enterprises. Otherbeneficiaries are the people who obtain advantages from a clearer and less pollutedsurrounding environment.The paper presents the results obtained from the application of the model in some pilotcases.